2020
DOI: 10.1007/s00134-020-06273-2
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Inflammatory Multisystem Syndrome Temporally-Associated with SARS-CoV-2 Infection: An Overview

Abstract: In spring 2020 paediatricians working across Europe and the USA [1] alerted colleagues to clusters of previously healthy children presenting with unremitting fever, multisystem inflammation and pancarditis. This syndrome, initially termed Inflammatory Multisystem Syndrome Temporally Associated with SARS-CoV-2 infection (PIMS-TS), or by its US variation Multisystem Inflammatory Syndrome in Children (MIS-C; Table 1), appears to be a rare complication of (largely) asymptomatic SARS-CoV-2 infection in children [8]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 15 publications
1
53
0
6
Order By: Relevance
“…One plausible explanation for this is that antibody concentrations may have decayed to below the threshold of detection by the time testing was clinically available in our patients. 10 Alternatively, antibody specificity and concentrations are known to differ in children with PIMS-TS in comparison to adults with COVID-19, 11 explaining an incomplete seroprevalence in this PIMS-TS cohort. Seronegative patients with PIMS-TS were phenotypically similar to seropositive patients with PIMS-TS, presented in the period of the first surge of cases in the UK COVID-19 pandemic, and were negative by PCR and relevant serology to extensive virologic testing.…”
Section: Discussionmentioning
confidence: 97%
“…One plausible explanation for this is that antibody concentrations may have decayed to below the threshold of detection by the time testing was clinically available in our patients. 10 Alternatively, antibody specificity and concentrations are known to differ in children with PIMS-TS in comparison to adults with COVID-19, 11 explaining an incomplete seroprevalence in this PIMS-TS cohort. Seronegative patients with PIMS-TS were phenotypically similar to seropositive patients with PIMS-TS, presented in the period of the first surge of cases in the UK COVID-19 pandemic, and were negative by PCR and relevant serology to extensive virologic testing.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment includes IV immunoglobulin ( 12 ), high-dose IV corticosteroids, and control of hypercytokinemia. For the control of hypercytokinemia, the use of interleukin-1 (IL-1) ( 13 ) antagonist (anakinra) and interleukin 6 (IL-6) receptor antagonist (tocilizumab) ( 14 ) has been suggested. Recent studies in SARS-CoV-2 patients have shown that these antagonists do not improve mortality ( 15 19 ), and tocilizumab has been associated with an increased risk of nosocomial infections ( 20 ).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…At present, professionals remain confronted with substantial uncertainties regarding clinical phenotypes, long-term outcomes, and optimal management ( 20 ). In the absence of randomized trials, evidence for best treatment is minimal for the diagnostic, anti-inflammatory, anti-infectious, and supportive measures which have been proposed ( 9 , 21 ). Recommendations therefore are based primarily on expert opinion and similar recommendations in the United Kingdom.…”
Section: Statement Of Uncertaintymentioning
confidence: 99%